1999
DOI: 10.1385/endo:11:1:37
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypoxia on Plasma Leptin and Insulin in Newborn and Juvenile Rats

Abstract: Hypoxia leads to a decrease in food intake and attenuated weight gain in rats. The purpose of this study was to measure plasma leptin and insulin in young rats exposed to hypoxia for 7 d as compared to a normoxic control group of the same age. One group was exposed from birth to 7 d of age; the other was exposed from 28 to 35 d of age (weaned at 21 d of age). As expected, body weight was significantly lower in rats of either age exposed to hypoxia for 7 d. Plasma leptin was significantly lower in hypoxic (2.0+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 15 publications
6
38
0
Order By: Relevance
“…The findings of growth retardation and increased adiponectin in this study, and insulin resistance in previous experiments using the same treatment paradigm ( 7,9,12 ), are similar to a variety of other pathophysiological states including prenatal growth restriction ( 25 ) and anorexia or bulimia nervosa ( 26,27 ). This "paradoxical" increase in adiponectin may be a response to, rather than a cause of, changes in insulin resistance.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The findings of growth retardation and increased adiponectin in this study, and insulin resistance in previous experiments using the same treatment paradigm ( 7,9,12 ), are similar to a variety of other pathophysiological states including prenatal growth restriction ( 25 ) and anorexia or bulimia nervosa ( 26,27 ). This "paradoxical" increase in adiponectin may be a response to, rather than a cause of, changes in insulin resistance.…”
Section: Discussionsupporting
confidence: 85%
“…It is possible that the marked increases in adiponectin in the current study were in response to the decrease in insulin sensitivity we have previously demonstrated ( 7,9,12 ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our data do suggest that some factor(s) other than ACTH may be causing the increased corticosteronogenesis and adrenal weight in hypoxic pups. Because increased leptin has been shown to inhibit corticosterone but not aldosterone production in adult rats (20), it is possible that a decrease in leptin that we have demonstrated in hypoxic rat pups (24,25) allowed an increased steroidogenic response in the ZF/R but not the ZG.…”
Section: Discussionmentioning
confidence: 85%
“…Although these beneficial effects are numerous, several are worth special mention. One effect we have demonstrated involving increased corticosterone is a significant decrease in insulin sensitivity (24,25). This is likely to maintain glucose delivery to the brain and heart under hypoxic conditions.…”
Section: Perspectivesmentioning
confidence: 78%